In vitro performance of injectable chitosan-tripolyphosphate scaffolds combined with platelet-rich plasma - Shimojo, Andréa Arruda Martins (Tissue Eng Regen Med, 2016)
This study aimed to evaluate the in vitro biological effectiveness of chitosan microparticles crosslinked with sodium tripolyphosphate (TPP) in combination with activated pure platelet-rich plasma (aP-PRP) as an injectable composite scaffold for growth factors release, cell proliferation and osteogenic differentiation. Two main novelties were addressed in the field of scaffolds in regenerative medicine: the first is the approach including simultaneously the three vertices of the proliferation triangle formed by the capabilities genic progenitor cells, conductive scaffolds and inductive growth factors, which are provided by platelet rich plasma (PRP); secondly, the approach of an injectable composite scaffolds formed by the fibrin network from aP-PRP and the chitosan microparticles crosslinked with TPP. The microparticles were prepared by vortexing the chitosan and TPP solutions. The ionic crosslinking of chitosan with TPP was made at mass ratios of 2:1, 5:1, and 10:1 at pH 4.0. P-PRP was obtained via the controlled centrifugation of whole blood. The composite scaffolds were prepared by adding the microparticles to immediately activated P-PRP. The results showed that the microparticles had adequate physicochemical and mechanical properties for injection. Furthermore, the microparticles controlled the release of growth factors from P-PRP. The proliferation of human adipose-derived mesenchymal stem cells was lower than in aP-PRP alone but significant at a 2:1 chitosan-TPP mass ratio. Osteogenic differentiation was stimulated at all studied mass ratios, as indicated by the alkaline phosphatase activity. These results offer perspectives for optimizing the composite scaffold, and to prove its potential as an injectable scaffold in regenerative medicine.